Digitalisasi Manajemen Produksi dan Keuangan pada Usaha Kecil di Pangkalpinang, Kabupaten Bangka - Wahyudie, Ilham Ary; Afriansyah, Riki; Rodika, Rodika; Sukanto, Sukanto (Indonesian Journal of Society Engagement, 2024)
Small and Medium Enterprises (UKM) in Pangkal Pinang, Bangka, often need help managing production and finance due to limited application of information technology. To overcome the problems of managing production and finance, this community service activity was carried out to implement the "TACON" management information system application in several selected UKM. The method of implementing the activity includes identifying UKM in need, training them to use the application, implementing the system, and monitoring and evaluating its impact. The activity results showed increased operational efficiency, where the production process became more organized, and financial transparency increased with more accurate recording. In addition, the training provided also improved the competence of human resources in the related UKM. The main contribution of this activity is to strengthen the competitiveness of UKM in Pangkalpinang by applying appropriate information technology and providing a solid foundation for UKM in facing future business challenges. This program proves that, when appropriately implemented, information technology can be an effective tool in supporting the sustainability and growth of UKM.